PENGEMBANGAN KURIKULUM DASAR DAN TUJUANNYA - Syamsul Bahri (Islam Futura, 2011)
Curriculum development is important to be investigated from various perspectives. This study will discuss twofold fundamental aspect of curriculum development; the basic and the purposes of curriculum. The literarure discussion reveals that the curriculum provided by a school not only limited to unit of courses and teaching learning process but also on all process which influence the development and student character building as it is required by national education goals. There are some elements such as Philosophy, Psycology, socio-culture and technology in which they support the foundation of curriculum. The objective of curriculum can be clasified into two group; micro and macro. The earlier is more consent on the institutional and intructional objectives. Whilts the latter is intended to reconstruct and to innovate any shortcoming of previous curriculum. The curriculum development aims at addaptating between education and social change and also exploring untouch knowledge.